Guillain-Barre Syndrome, Clinical Spectrum and Electrophysiological Sub Types: A Local Experience - Faryal Shamim; Safia bano safia; Masooma Waqar; Ahsan Numan (Shalamar Medical & Dental College, Lahore, Pakistan, 2023)
Background: Guillain-Barre syndrome is uncommon neurological disease that occurs in acute phase as generalized polyradiculo-neuropathy. It has multiple variants some of them being uncommon and rarely encountered. Objective: The objective of the study was to determine the frequency and clinical characteristics of Guillain-Barre syndrome variants. Methods: A cross-sectional study was carried out in neurology department, Mayo hospital from July to December 2022. Patients clinically diagnosed as Guillain-Barre syndrome by using Brighton criteria were included. All the patients underwent electro diagnostic procedures and they were categorized into five basic variants i.e., Acute motor axonal neuropathy, Acute motor sensory axonal neuropathy, acute inflammatory demyelinating polyradiculo-neuropathy, acute sensory axonal neuropathy and mixed variety acute polyradiculo-neuropathy. Results: Out of total 85 patients, males were 56 (65.9%) and 29 (34.1%) were females. Adults were more affected with a mean age of 36±15.3.  Frequency of acute motor axonal neuropathy (35.3%) was high followed by acute motor sensory axonal neuropathy (31.8%), mixed variety acute polyradiculo-neuropathy (16.5%), acute inflammatory demyelinating polyradiculo-neuropathy (12.9%) and acute sensory axonal neuropathy (3.5%) respectively. Conclusion: Acute motor axonal neuropathy is frequently encountered Guillain-Barre syndrome variant in our setup. Also, the frequency of acute sensory axonal neuropathy and mixed variety acute polyradiculo-neuropathy has increased with a declining trend of acute inflammatory demyelinating polyradiculo-neuropathy.